Python Machine Learning Blueprints : Put your machine learning concepts to the test by developing real-world smart projects, 2nd Edition /: Put your machine learning concepts to the test by developing real-world smart projects, 2nd Edition. (2019) - Combs, Alexander; Roman, Michael
No abstract available